The tonal webern: a physiognomy of early modernism - Wedler, S (2017)
As a consequence of the elevation of Anton Webern as the figurehead of atonality and a precursor to post-war serialism, the composer’s tonal repertoire has been widely regarded as embarrassing works of juvenilia and so merely a parergon to what was yet to come, to the extent that it has remained little known and understudied up to this day. The first extensive account of Webern’s tonal music (1899–1908), this dissertation explores the complex and variegated ways in which the young Webern engaged with, and sought actively to contribute to, the cultural ideas and discourses of turn-of-the-century modernism, well before he would self-consciously embark upon his famous ‘path’ to the New Music. Through close study of key works such as the symphonic tone poem Im Sommerwind, the ‘Segantini’ string quartet, and the Passacaglia for large orchestra op. 1 in light of recent developments in the theory and analysis of late nineteenth-century tonal music (sonata deformation theory, extended Schenkerian techniques, and neo-Riemannian transformations), each chapter illuminates a unique aspect of Webern’s early modernist imagination. Providing a wealth of new historical and philological insights from the manuscripts, sketches, and biographical documents archived at the Paul Sacher Foundation, this study addresses Webern’s aesthetic interest in the evocation of atmosphere and lyrical temporality, the Zarathustrian meaning-strata embedded in his musical language, the formal functions of his use of energetic waves, and his revisionary understanding of Viennese Classicism at a time when Vienna was precariously poised between historicist tendencies on the one hand and attempts at a radical reformation of the past on the other. The discussion is framed by a post-Adornian/post-Dahlhausian concern for a critical reappraisal of the category of ‘early style’. While acknowledging the rapid stylistic transformation that Webern’s tonal language underwent, shaped in particular by his studies with Arnold Schoenberg from 1904–1908, it will be suggested that ‘earliness’ in Webern is not simply a chronological term but is rather best understood in terms of a constitutive tension between phenomenological and dialectical modes of musical thought – a tension which had crystallised at the turn-of-the-century as essentially irreconcilable and yet formed the discursive matrix though which much of Webern’s aesthetic physiognomy was shaped. In this way, this dissertation is as much a study of the generative elements of Webern’s musical imagination as it is a study of the intellectual milieus of Viennese modernism.